2022
DOI: 10.3390/ijms231912034
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Glu-D1 Alleles and Novel Marker–Trait Associations for Flour Quality and Grain Yield Traits under Heat-Stress Environments in Wheat Lines Derived from Diverse Accessions of Aegilops tauschii

Abstract: Heat stress during grain filling is considered one of the major abiotic factors influencing wheat grain yield and quality in arid and semi-arid regions. We studied the effect of heat stress on flour quality and grain yield at moderate and continuous heat stress under natural field conditions using 147 lines of wheat multiple synthetic derivatives (MSD) containing Aegilops tauschii introgressions. The study aimed to identify the marker–trait associations (MTAs) for the quality traits and grain yield under heat-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 89 publications
1
0
0
Order By: Relevance
“…Near significant marker wsnp_Ex_c35886_43950102, the TraesCS1D02G159700 gene encoding the seed storage protein was located, which suggests that the locus may belong to Glu-D1. A similar locus containing the TraesCS1D02G159700 gene was discovered by Mohamed et al [58] when studying the wheat lines obtained from crosses with various accessions of Aegilops tauschii. In another research by Deng et al [54], two pleiotropic loci associated with GC and gluten index were identified using the DArT and SSR markers in chromosome 1D in marker interval Glu-D1-wPt3743.…”
Section: Comparison Of Putative Qtl Localization With Known Datasupporting
confidence: 55%
“…Near significant marker wsnp_Ex_c35886_43950102, the TraesCS1D02G159700 gene encoding the seed storage protein was located, which suggests that the locus may belong to Glu-D1. A similar locus containing the TraesCS1D02G159700 gene was discovered by Mohamed et al [58] when studying the wheat lines obtained from crosses with various accessions of Aegilops tauschii. In another research by Deng et al [54], two pleiotropic loci associated with GC and gluten index were identified using the DArT and SSR markers in chromosome 1D in marker interval Glu-D1-wPt3743.…”
Section: Comparison Of Putative Qtl Localization With Known Datasupporting
confidence: 55%
“…The results showed that a number of superior lines could be identified under various conditions and for different climate-resilient traits [15,16,18,24,25]. Moreover, GWAS analysis identified several MTAs under heat, drought, and heat-drought conditions [15,16,19,20,25]. Following the identification of several heat-tolerant lines from the MSD population, backcross inbred lines (BILs) were developed in the background of those heat-tolerant lines with exotic alleles from two Ae.…”
Section: Discussionmentioning
confidence: 99%
“…; abbreviated as WA). For more details on the characteristics of the experimental sites at DN and GRSF, refer to Elbashir et al [23] and Mohamed et al [19]. The Waha site is characterized as a semi-arid area with mostly haplusterts soil type, clay loam in texture, with pH range of 7.5-8.0, low N (0.05-0.20%), and low available P (30-60 kg ha -1 ) (http://susis.sd/south-region-0-30/, accessed on November 12, 2023).…”
Section: Experimental Sites and Designmentioning
confidence: 99%
See 2 more Smart Citations